Alfabetização Científica em diálogo com Tertúlias Dialógicas Científicas: aproximações e conciliações - Freire, Maria Júlia (2023)
Scientific Literacy (SL) is a current paradigm for Science Education and recognizing that access to scientific knowledge is a necessity for all. Considering that the Scientific Dialogic Tertulia (SDT) is a successful educational approach internationally validated, capable of contributing to the overcoming of educational inequalities by ensuring access to scientific knowledge produced by humanity and understood as a methodological possibility for SL, the overall objective of this research was to compare SDT and SL based on the most cited Brazilian scientific papers in Google Scholar within the scope of Scientific Literacy. For this purpose, the Bibliographic Research method was used, exploring works that mentions or refer to “Scientific Literacy”. To analyze the corpus, the Content Analysis method was applied, the Dialogic Learning, foundations of Dialogic Tertulias, and Freire’s contributions to literacy served as the reference. The analysis categories, consisting mile concern to the concept, conditions, and promotion of SL. The results confirmed that (a) SL can be understood as a lifelong process for learners, and (b) SL shares similarities with SDT as both are seen as ongoing processes that allow for a contextualized approach and emphasize the instrumental dimension of learning, with professors being essential to this process. Thus, the Scientific Dialogic Tertulia is understood as a methodological proposal for teaching in alignment with Scientific Literacy.